Oxidation products of arsenopyrite and other sulfides from the ore deposit Sastavci, Serbia - Jelić, Ivana; Stojanović, Jovica; Pačevski, Aleksandar; Vuković, Nikola; Zdravković, Alena; Radosavljević-Mihajlović, Ana; Kašić, Vladan (Mining and Metallurgy Institute, Bor, 2024)
The dominant sulfide minerals of the Pb-Zn deposit Sastavci are arsenopyrite, galena, and sphalerite. Oxidation of arsenopyrite can lead to the release of arsenic, a highly toxic environmental element. Oxidation products of arsenopyrite and other sulfides, present in the ores themselves as well as on the surfaces of samples, were analyzed by the OL microscopy in reflected light, SEM-EDS, and XRPD methods. It was established that scorodite and Fe sulfo-arsenates are the main alteration products of arsenopyrite. The Znand Mn-sulfates form crusts and aggregates on the surfaces of some samples. The conclusion is that the main concentrations of released As are found in scorodite, a relatively stable mineral in the surface conditions, and to a lesser extent in arsenolite.
Keywords: oxidation products; Fe sulfo-arsenate; sulfates; scorodite; Sastavci